PEMANFAATAN FASILITAS SERTIFIKAT HALAL JALUR SELF DECLARE UNTUK PELAKU USAHA MIKRO DAN KECIL DI ACEH - Saiful Bahgia; Hasbi; Hamdani (JURNAL KREASI RAKYAT, 2023)
This activity aims to facilitate one of the distribution permits for micro and small business products, namely free halal certification for micro and small business actors. The micro-business actors involved and taking part in the activities are business actors in Banda Aceh, Aceh Besar, Pidie, Aceh Jaya, and Southeast Aceh, totaling 25 micro and small business actors (UMK). Facilitate the application of 20 Free Halal Certificates (SH) for MSEs in Aceh. The results of this activity are: educating the MSME community about the importance of distribution permits; MSEs understand the procedures for Halal Product Processing (PPH); The MSE community understands the procedures for applying for SH through the SEHATI 2023 Program, the self-declare route on a SIHALAL account. Free SH counseling and assistance for MSE products in Aceh can increase product marketing and increase public enthusiasm for obtaining halal certificates.